The Influence of Profitability, Capital Structure, and Company Size on the Company Value of the Coal Sub-Sector in 2021-2025 - Aini, Aisyah; Arum Janie, Dyah Nirmala (Dinasti Publisher, 2026)
This study aims to determine the effect of profitability, capital structure, and company size on company value in mining sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2025 period. This study uses a quantitative method with a purposive sampling technique. The number of samples used is as many as mining sector companies that meet the research criteria during the 2021-2025 observation period. The data used is secondary data obtained from the company's annual financial reports published through the Indonesia Stock Exchange. The data analysis method used is panel data regression with the help of the EViews program. The dependent variable in this study is company value proxied by Price to Book Value (PBV), while the independent variables include profitability proxied by Return on Assets (ROA), capital structure proxied by Debt to Equity Ratio (DER), and company size proxied by Ln Total Assets. The results of the study indicate that profitability has a significant positive effect on company value, capital structure has a significant negative effect on company value, while company size has a positive effect on company value. These findings indicate that a company's ability to generate profits and optimal capital structure management are important factors in increasing company value in the mining sector.